Role Conflict, Self Efficacy, Employees’ Performance and Organizational Performance - Hadi Kurnia Fahmi; Said Musnadi; Nadirsyah Nadirsyah (Journal of Accounting Research, Organization and Economics, 2019)
AbstractObjective – This study aims to analyze the influence of role conflict and self-efficacy towards employees’ performance and its implications on organizational performance at Inspectorate of Nagan Raya District, Aceh, Indonesia. Design/methodology – The sample of this study is 120 auditors. The data was collected through questionnaire and analyzed using Structural Equation Model (SEM). Results – The study found that role conflict and self-efficacy have positive and significant influence on employees’ performance and inspectorate performance at Nagan Raya District. Meanwhile employees’ performance mediates the effect of role conflict and self-efficacy towards inspectorate performance at Nagan Raya District.